Factors influencing music teaching among primary and early childhood education and care generalist teachers: a meta-narrative review - Nguyen, Thomas; Knigge, Jens; Sæther, Morten; Oravec, Lina (Frontiers in Education, 2025)
A growing body of research has explored factors influencing music teaching among pre-service and in-service generalist teachers in primary and early childhood education and care (ECEC). To synthesise this diverse field, we conducted a systematic meta-narrative review, identifying six overarching meta-narratives across 249 peer-reviewed studies from 38 countries (1995–2023). Using clear inclusion criteria, systematic searches, quality appraisals, and iterative analysis, and framed by the Model of the Determinants and Consequences of Teachers’ Professional Competence, our meta-narratives shed light on the individual and contextual factors influencing generalist teachers’ music-teaching competence and strategies, as well as how various teacher-training approaches have integrated these factors to support their professional development as music teachers. We explore general tendencies, commonalities, and discrepancies across studies, offering insights into the professional development of music-teaching generalists, and provide recommendations and outline implications for policymakers, researchers, and educators.